Peran Self- Efficacy dalam Memediasi Penggunaan E - Commerce dan Literasi Digital Terhadap Keberlanjutan UMKM di Kota Denpasar - Kadek Krisna Diva Antara,; Gede Crisna Wijaya, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector play a strategic role in supporting the economy of Denpasar City. However, the increasingly competitive business environment requires entrepreneurs to adapt to digital technological advancements in order to sustain their businesses. This study aims to analyze the effects of e-commerce usage and digital literacy on MSME sustainability, as well as to examine the mediating role of self-efficacy. This research employed a quantitative approach with a causal associative design. The sample consisted of 99 food and beverage MSME owners in Denpasar City, selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that e-commerce usage, digital literacy, and self-efficacy have positive and significant effects on MSME sustainability. Furthermore, e-commerce usage and digital literacy were found to positively and significantly influence self-efficacy. Self-efficacy also significantly mediates the relationship between e-commerce usage, digital literacy, and MSME sustainability. These findings indicate that MSME sustainability is determined not only by the adoption of digital technology and digital literacy capabilities but also by entrepreneurs’ confidence in their ability to effectively manage and utilize technology. Therefore, strengthening digital competencies and enhancing self-efficacy are essential factors in supporting MSME sustainability in the digital economy era.